Long-Term Care and Lazy Rotten Kids - Helmuth Cremer; Kerstin Roeder (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the determination of informal long-term care (family aid) to dependent elderly in a worst case scenario concerning the harmony of family relations. Children are purely selfish, and neither side can make credible commitments (which rules out efficient bargaining). The model is based on Becker's rotten kid specification except that it explicitly accounts for the sequence of decisions. In Becker's world, with a single good, this setting yields efficiency. We show that when family aid (and long-term care services in general) are introduced the outcome is likely to be inefficient. Still, the rotten kid mechanism is at work and ensures that a positive level of aid is provided as long as the bequest motive is operative. We identify the inefficiencies by comparing the laissez-faire (subgame perfect) equilibrium to the first-best allocation. We initially assume that families are identical ex ante. However, the case where dynasties differ in wealth is also considered. We study how the provision of long-term care (LTC) can be improved by public policies under various informational assumptions. Interestingly, crowding out of private aid by public LTC is not a problem in this setting. With an operative bequest motive, public LTC will have no impact on private aid. More amazingly still, when the bequest motive is (initially) not operative, public insurance may even enhance the provision of informal aid.
Keywords: D13; H21; I13; 330; rotten kids; long-term care; family aid; optimal taxation